Impacto del acceso a los servicios de agua y alcantarillado en anemia en niños menores de 5 años en Perú - Guzmán-Castillo, Wagner (2021)
Anemia is a multidimensional problem that worsens at an early age. When anemia prevalence rates exceed 40 %, the WHO recognizes it as a serious public health problem. In Peru, infants between the ages of 6 and 36 months have anemia in 43,5 % of urban areas and 51,1 % of rural areas. The objective of the study was to determine the impact of access to water and sewerage on anemia, for this, we used the Propensity Score Matching as an impact evaluation technique and through the use of data from the Endes 2019. The results show that in general, having with access to water and sewage contributes to reducing the presence of this disease. We conclude that in general, having water and sewage services has an impact on reducing anemia by 14,6 % in households with children under 5 years of age, particularly, having only water services contributes to a decrease of 12,4 % and having only a sewage service reduces anemia in this group by 7,6 %. When comparing the impact of access to these two services on anemia according to urban and rural areas, this is greater in the urban area and when only the water service is accessed, which would be related to the greater incidence of chlorination actions.